A decoherence-free subspace in a charge quadrupole qubit - Mark Friesen (Nature Portfolio, 2017)
Robust implementations of semiconducting qubits require overcoming the effects of charge noise, which limits coherence times. Here the authors propose a decoherence-free subspace for charge qubits to protect them from uniform electric field fluctuations, proposing an implementation in a triple quantum dot.